FINITE DIFFERENCE METHODS FOR COMPUTING EIGENVALUES OF FOURTH ORDER BOUNDARY VALUE PROBLEMS - Usmani, Riaz A. (International Journal of Mathematics and Mathematical Sciences, 1986)
This brief report describes some new finite difference methods of order 2 and 4 for computing eigenvalues of a two point boundary value problem associated with a fourth order linear differential equation y^(4) (p(x)- λq(x))y =0. These methods are derived from the formula h^4y_1^(4) (δ^4 -1/6 δ^6+7/240 δ^8-….)y_i Numerical results are included to demonstrate practical usefulness of our methods.